Study on functionalized acidic imidazolium‐based ionic liquids as effective adsorbents for HCHO storage. Issue 1 (17th October 2022) - Guo, Xin; Ren, ChunXiao; Jiang, Siqi; Li, Jisheng; Zhang, Shuai; Wang, Yichuan; Ma, Weiting; Yang, Ye; Ma, Chenglong; Su, Zhiyong; Wang, Zhiyuan; Hu, Yufeng; et al.
Abstract: BACKGROUND: Recent works have shown how to develop methods with specific economic and environmental aspects; this is the main motivation for research on energy efficient processes and environmentally friendly materials for formaldehyde (HCHO) storage. One specific goal is to improve the adsorption capacity for HCHO by constructing closely contacted connections with absorbents. RESULTS: In this study, two ionic liquids (ILs), 1‐methylimidazole hydrogen sulfate [MIM][HSO4 ] and Imidazole hydrogen sulfate [IM][HSO4] as newly developed absorbents for HCHO storage are applied for the first time. Based on thermogravimetric analysis (TGA) and nuclear magnetic resonance (NMR) results, it is concluded that their exceptional capacity for storage of HCHO is 31.07 and 34.60 (g formaldehyde)⋅(mol ionic liquid) −1, respectively. In addition, to study the renewability of HCHO, the decomposition rates of the reaction products (as a function of decomposition time and decomposition temperature) were measured. The optimal kinetic model was selected to satisfy the formation and decomposition processes of the products. Thereafter, the activation energy ( E ), pre‐finger factor ( A ), decomposition rate constant of the decomposition reaction, and the rate constant of the reaction were determined. NMR results confirmed that the higher storage capacity of HCHO in [MIM][HSO4 ] and [IM][HSO4 ] is mostly attributed to the stronger covalent bonds between the ionic liquids (ILs) and HCHO. CONCLUSION: These ILs are, thus, promising candidates as adsorbents for the design of air depollution processes. This study may provide new insights into the use of ILs for storage of HCHO for low‐cost, high‐performance, and environmentally benign adsorbents for indoor air purification. © 2022 Society of Chemical Industry (SCI).